2002
DOI: 10.1097/00000539-200207000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Anesthetic Considerations in Patients with Ventricular Assist Devices Presenting for Noncardiac Surgery: A Review of Eight Cases

Abstract: The number of patients supported by ventricular assist devices (VADs) that present for noncardiac surgery is increasing in our institution. Our recent experience with eight such patients is reported, along with a review of the most commonly implanted VADs and the anesthetic implications and considerations for VAD-supported patients undergoing noncardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 12 publications
1
56
0
1
Order By: Relevance
“…In studies involving a variety of noncardiac operations, arterial line use was highly variable and ranged from none to all patients with LVADs having invasive arterial line BP monitoring intraoperatively. 5,7,8,13,14,25,26 Goudra et al 14 reported that no invasive arterial lines were used in their retrospective series of 68 GI endoscopies on patients with LVADs. However, the authors reported that pulsatile flow was present in all patients and that conventional nIBP cuff readings were possible in all patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies involving a variety of noncardiac operations, arterial line use was highly variable and ranged from none to all patients with LVADs having invasive arterial line BP monitoring intraoperatively. 5,7,8,13,14,25,26 Goudra et al 14 reported that no invasive arterial lines were used in their retrospective series of 68 GI endoscopies on patients with LVADs. However, the authors reported that pulsatile flow was present in all patients and that conventional nIBP cuff readings were possible in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous series have described the perioperative management of patients with LVAD undergoing noncardiac surgery, some of which have included GI endoscopies. [5][6][7][8][9][10][11][12][13] However, publications on patients with LVADs exclusively undergoing GI endoscopies are limited to one retrospective series that did not include postprocedure outcomes. 14 The purpose of this study was to retrospectively review the periprocedural management and postprocedure complications of patients with LVADs undergoing GI endoscopies at a single, large tertiary referral center.…”
mentioning
confidence: 99%
“…24 The most frequently reported complication in these patients is postoperative bleeding due the necessary anticoagulation therapy required for the VAD in order to avoid thromboembolic events. 22,25,26 Many of these patients require hospital admission prior to elective operations and conversion from warfarin to heparin anticoagulation, which can be stopped or reversed in the immediate perioperative period. In emergency procedures, such as with these two patients, transfusion of fresh frozen plasma is required to acutely correct the patient's chronic anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Einige operative Eingriffe erfordern eine spezielle Lagerung des Patienten, wie z. B. die laterale Dekubitusposition bei der Nephrektomie [37]. Sowohl die genannte Lagerung als auch eine Hypovolämie [37] sind mögliche Ursachen für eine Hypotension bei VAD-Patienten [5].…”
Section: Hämodynamische Komplikationenunclassified